Acute inferior myocardial infarction in a patient with a prosthetic aortic valve and high international normalized ratio - ATAŞ, HALİL; SARI, İBRAHİM; DELİL, KENAN (TERMEDIA PUBLISHING HOUSE LTD, 2014)
ST elevation acute myocardial infarction in patients with a mechanical prosthetic valve is rare and usually due to inadequate anticoagulation. We present a case of acute inferior myocardial infarction in a patient with a prosthetic aortic valve and high international normalized ratio, which has not been reported previously.
Keywords: myocardial infarction; prosthetic valve; international normalized ratio; FACTOR-V-LEIDEN